Estigma Internalizado entre dependentes de álcool e crack em tratamento no Brasil - Silveira, Pollyanna Santos da [UNIFESP] (2014)
Drug dependence is considered one of the most stigmatizing health conditions. Growing evidences have shown that stigma is associated with different impairments to stigmatized individuals. In order to widen the knowledge on the theme, the current study was organized in three different studies. Study 1 aimed to review the scientific literature in the studied field. Searches were done in sources such as Psycinfo, Pubmed, web of Knowledge and Scopus, using the keywords “self-stigma” and “internalized stigma”. It was observed the increase in the amount of publications since the first publication in 2003. The studies revealed socio-demographic (gender, age, employment, school level and family income) and psycho-social (assigning responsibility, angst and perception of devaluation) features associated with internalized stigma. Among the consequences of internalized stigma, the following psychological implications were observed: low willingness to search for help, adoption of healthy behaviors, low adhesion to treatment, worsening of symptoms, low quality of life, expectation over rejection, discrimination, isolation and social avoidance. In regards to coping strategies, cognitive restructuration, empowerment, larger social contact, attitude changing as well as the sense of belonging to a group were stood as effective means to avoid stigma internalization or a way to face it. Study 2 aimed to assess the relation between internalized stigma and psycho-social features. The used instruments were: (a) ISMI adapted for Substance Dependents; (b) MINI; (c) CES-D; (d) Herth Hope Scale (HHS) and (e) Rosenberg Self-esteem Scale. The sample comprised 461 substance dependents that had looked for treatment. Among the sample members, 35.8% just used alcohol, 33.6% alcohol and crack and 30.6% crack. The associations among variables were analyzed by means of multiple linear regression, adopting internalized stigma as outcome variable and the other explanatory variables were organized into three blocks (socio-demographic, psycho-social and type of dependence). The socio-demographic model presented adequate data adjustments and explained about 4% of the variance in ISMI scores, but only gender, kind of used drug and the status of employment have significantly helped the explanation. The psychological model explained 31% of the variance. The third model held all the variables and explained 34% of the variances. Self-esteem, hope, depression and occupational status were strongly associated with the internalized stigma. Study 3 aimed to study the internalized stigma and other psycho-social aspects throughout the first month of treatment among crack dependents. The following instruments were used: (a) ISMI adapted to Substance Dependents; (b) MINI; (c) CES-D; (d) Herth Hope Scale (HHS); (e) Rosenberg self-esteem Scale; (f) Social Support; and (g) Socio-demographic questionnaire. The sample comprised 114 crack dependents who joined a treatment service and, after a month, patients who were still undergoing treatment (N=29) were interviewed again. The comparison between answers from before and after 30 days treatment showed that there was a decrease on depression symptoms and an increase on hope. No statistically significant differences were verified for all the studied variables among patients who had abandoned treatment when compared to those who had acceded to it. Differently from what was expected, internalized stigma was not an abandonment predictor. Based on the performed studies, it was possible to observe that internalized stigma among substance dependents is associated with a complexity of psycho-social factors. Stigma was not configured as abandonment predictor in the first month of treatment for crack dependents. However, literature data point towards other significant impairments for these individuals, mainly as an obstacle in treatment previous stages, thus deserving attention on further studies in drug dependence fields.